Towards A Networked Privacy Paradigm: Assumptions And Implications - De Wolf, Ralf Patrick; Heyman, Rob (AoIR Selected Papers of Internet Research, 2017)
There is a long tradition of research on why and to whom people disclose information and manage their privacy, especially since the emergence of social media. Recently, there has been a push to conceptualize privacy in relation to social media as ‘networked privacy’, where privacy is framed in terms of networks, relationships or people. Despite the popular term it is unclear what makes networked privacy new and how it relates to other privacy conceptualizations. In this paper, we therefore analyze networked privacy together with the following privacy theories; Warren and Brandeis’ right to be left alone, Westin’s privacy control, Nissenbaum’s theory of contextual integrity and Petronio’s communication privacy management theory. Each theory refers (implicitly or explicitly) to different ontological and epistemological claims and we will clarify these and illustrate how fundamentally different the networked privacy paradigm is from its counterparts. The analysis serves as a first step towards defining fundamental principles for a paradigm of networked privacy.